Emotional labor of employees in selected fast food restaurants in Metro Manila - Medino, Jennifer B.
This study examined the emotional labor (EL) of fast food employees in Metro Manila, Philippines, in connection with their performance of emotional labor-related behaviors (ELRBs) required by their roles. It also explored the factors influencing the employees’ EL and its impact on their well-being and job performance. Additionally, the research investigated the coping strategies employed by these employees, as well as the programs and practices implemented by the management that support them in managing emotional labor. This research employs an exploratory and descriptive design, utilizing a mixed-methods approach for data collection. It was conducted before and during the COVID-19 pandemic to compare the impact of both periods. The quantitative approach was done through a survey using a five-part self-administered questionnaire. The respondents, consisting of cashiers, dining crew, delivery riders, and party hosts, were chosen using convenience sampling. Meanwhile, qualitative data were obtained using a Focus Group Discussion (FGD) with fast food employees. Fast food managers were also interviewed before the pandemic to gather further insights and validate information related to management programs and company requirements relevant to the study. Descriptive statistics, Spearman's Rho, and Mann-Whitney tests were used to analyze survey data collected from 262 employees prior to the pandemic and 81 employees during the pandemic. The results were analyzed alongside the findings from the FGD and interview. Results revealed that various individual, sociocultural, and organizational factors were associated with surface acting, deep acting and genuine acting, which in turn impacted employees' well-being and job performance. Employees engaged in genuine acting and deep acting more than surface acting, signifying their overall job satisfaction, alignment with their frontline roles, and their ability to effectively contribute to frontline operations.